2019
DOI: 10.4103/ijo.ijo_1317_18
|View full text |Cite
|
Sign up to set email alerts
|

Multicolor imaging findings in torpedo maculopathy

Abstract: We describe the multicolor imaging findings in two cases of Torpedo maculopathy (TM). Multicolor imaging can be a useful tool in identifying the level of retinal and choroidal layer involvement in TM. This imaging modality further confirms the hypothesis that TM is a localized congenital abnormality of retinal pigment epithelium pigmentation which leads to outer retinal and inner choroidal degeneration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…MC imaging signatures of torpedo lesions in the series coincided with data previously published by our group. [10] The etiology of torpedo-shaped lesions in the retina remains speculative. Due to the consistent location of torpedo lesions in previous reports of TM, the most commonly accepted hypothesis is a persistent defect in the development of RPE in the fetal temporal bulge.…”
Section: Discussionmentioning
confidence: 99%
“…MC imaging signatures of torpedo lesions in the series coincided with data previously published by our group. [10] The etiology of torpedo-shaped lesions in the retina remains speculative. Due to the consistent location of torpedo lesions in previous reports of TM, the most commonly accepted hypothesis is a persistent defect in the development of RPE in the fetal temporal bulge.…”
Section: Discussionmentioning
confidence: 99%
“…It has been widely used to describe the findings in various retinal and choroidal pathologies. 11,12 Multicolour imaging is a non-invasive retinal imaging modality that simultaneously acquires three reflectance images of the retina using three individual lasers, producing a composite image, thereby allowing analysis of changes at various levels within the retina. The information from these three images are integrated to form a composite multicolour image.…”
mentioning
confidence: 99%
“…Type 1 was defined by having attenuation of the outer retinal structures without retinal or inner choroidal cavitation; Type 2 featured attenuation of the outer retinal structures with subretinal cavitation. 97 Torpedo lesions that contain choroidal excavation were recently classified as type 3 TM by Tripathy et al and studied by Venkatesh et al [105][106][107] Cavitation appears as an optically empty space on OCT as a result of thinning or loss of the outer retinal layers or choroidal layers. The distinction between cavitation and a neurosensory detachment that occurs in some cases can be made on the basis of preservation of retinal layer thickness in a detachment and attenuation or loss in cavitation.…”
Section: Torpedo Maculopathymentioning
confidence: 99%
“…96 Similarly, it is unclear if the choroidal excavation seen in type 3 TM is acquired or part of the underlying mechanism pathophysiology. 107 While some authors have reported these lesions to be nonprogressive, 87 others have shown mild progression over time. 97 Wong et al hypothesized that the Type 1 subtype progressed to type 2 over time but reports of type 2 TM in patients as young as 5 years old cast doubt on that hypothesis.…”
Section: Torpedo Maculopathymentioning
confidence: 99%
See 1 more Smart Citation